Energy-efficient and noise-tolerant neuromorphic computing based on memristors and domino logic - Hendy, Hagar; Merkel, Cory (Frontiers in Nanotechnology, 2023)
We propose an energy-efficient architecture for neuromorphic computing based on memristors and domino logic. The design uses the delay of memristor RC circuits to represent synaptic computations and a simple binary neuron activation function. Synchronization schemes are proposed for communicating information between neural network layers, and a simple linear power model is developed to estimate the design's energy efficiency for a particular network size. Results indicate that the proposed architecture can achieve 1.26 fJ per classification per synapse and achieves high accuracy on image classification even in the presence of large noise.